Designing a multi‐component intervention (P3‐MumBubVax) to promote vaccination in antenatal care in Australia. (24th July 2020) - Kaufman, Jessica; Attwell, Katie; Hauck, Yvonne; Leask, Julie; Omer, Saad B.; Regan, Annette; Danchin, Margie
Abstract: Issue addressed: Coverage of maternal influenza and pertussis vaccines remains suboptimal in Australia, and pockets of low childhood vaccine coverage persist nationwide. Maternal vaccine uptake is estimated to be between 35% and 60% for influenza vaccination and between 65% and 80% for pertussis vaccination. Australian midwives are highly trusted and ideally placed to discuss vaccines with expectant parents, but there are no evidence‐based interventions to optimise these discussions and promote maternal and childhood vaccine acceptance in the Australian public antenatal setting. Methods: We gathered qualitative data from Australian midwives, reviewed theoretical models, and adapted existing vaccine communication tools to develop the multi‐component P3‐MumBubVax intervention. Through 12 interviews at two Australian hospitals, we explored midwives' vaccination attitudes and values, perceived role in vaccine advocacy and delivery, and barriers and enablers to intervention implementation. Applying the theory‐based P3 intervention model, we designed intervention components targeting the Practice, Provider and Parent levels. Midwives provided feedback on prototype intervention features through two focus groups. Results: The P3‐MumBubVax intervention includes practice‐level prompts and identification of a vaccine champion. Provider‐level components are a vaccine communication training module, learning exercise, and website with printable fact sheets. Parent‐level intervention components include text message reminders to receive influenza and pertussis vaccines in pregnancy, as well as online information on vaccine safety, effectiveness and disease severity. Conclusions: The P3‐MumBubVax intervention is the first Australian antenatal intervention designed to support both maternal and childhood vaccine uptake. A pilot study is underway to inform a planned cluster randomised controlled trial. So what?: Barriers to vaccine acceptance and uptake are complex. The P3 model is a promising evidence‐informed multi‐component intervention strategy targeting all three levels influencing health care decision‐making.